Eggshell membrane hydrolyzates activate NF-κB in vitro: possible implications for in vivo efficacy - Ruff KJ; Durham PL; O’Reilly A; Long FD (Dove Medical Press, 2015)
Kevin J Ruff,1 Paul L Durham,2 Austin O’Reilly,2 F Daniel Long1 1ESM Technologies, LLC, Carthage, MO, USA; 2Center for Biomedical and Life Sciences, Missouri State University, Springfield, MO, USA Purpose: Eggshell membrane (ESM) has been shown to contain naturally occurring bioactive components, and biological activities such as reducing proinflammatory cytokines, liver fibrosis, and joint pain in osteoarthritis sufferers have also been reported for ESM matrix as a whole. Nuclear factor kappa-light-chain-enhancer of activated B-cells (NF-κB) is a signaling protein found in the cytoplasm of nearly all human and animal cell types and is a primary regulator of immune function. The studies reported herein were designed to investigate the possible role that NF-κB activity might play in the reported biological activities of ESM. Methods: Three ESM hydrolyzates produced via fermentation, enzymatic, or chemical hydrolysis were evaluated in vitro in either human peripheral blood mononuclear cell or THP-1 (human leukemic monocyte) cell cultures for NF-κB activity following 4-hour exposure. The hydrolyzates were compared with untreated control cells or cells incubated with lipopolysaccharide or ascorbic acid. The source of ESM activity was also evaluated. Results: NF-κB levels were increased above levels found in untreated cells at all three dilutions (1:100, 1:1,000, and 1:10,000) for the fermentation hydrolyzate of ESM (ESM-FH) (P=0.021, P=0.020, P=0.009, respectively) in peripheral blood mononuclear cells. The enzymatic hydrolyzate of ESM (ESM-EH) also produced statistically significant levels of activated NF-κB at the 1:100 and 1:1,000 dilutions (P=0.004, P=0.006, respectively) but fell just shy of significance at the 1:10,000 dilution (P=0.073). Similarly, ESM-FH (P=0.021, P=0.002) and ESM-EH (P=0.007, P=0.007) activated NF-κB in THP-1 cells at 1:1,000 and 1:10,000 dilutions, respectively. The chemical hydrolyzate of ESM (ESM-CH) showed statistically significant levels of activation at the 1:1,000 dilution (P=0.005) but failed to differ from untreated cells at the 1:10,000 dilution (P=0.193) in THP-1 cells. Conclusion: Results from our studies provide evidence that ESM hydrolyzates significantly activate NF-κB, and the source of this activity was investigated to confirm that it is inherent to ESM and not derived from bacterial contamination. Based on our findings, we propose a plausible hypothesis as to how increased NF-κB activity might translate into the in vivo efficacy that has been observed with ESM via an “oral tolerance” mechanism. Keywords: eggshell membrane, NF-κB, lipopolysaccharide, polymyxin B, lipoprotein lipase, hydrolyzate